Implications of the Limits for Filing a Lawsuit to the State Administrative Court: Upholding Legal Certainty or Injuring Human Rights? - Zaharuddin Sani Ahmad Sabri; Muhammad Zaidan Syafiqy Akhmad (Universitas Negeri Semarang, 2023)
The State Administrative Court (PTUN) plays an important role in adjudicating state administrative conflicts, issuing final and impactful State Administrative Decisions (KTUN). Recipients aggrieved by these decisions have a 90-day window, as mandated by Article 55 of the Administrative Court Law (UU PTUN), to file a lawsuit if they believe the KTUN violates established laws, regulations, or principles of good governance. Despite its apparent procedural clarity, the 90-day timeframe has become a subject of public controversy, prompting four challenges to its constitutionality before the Constitutional Court. Critics argue that this stringent deadline, rather than achieving its intended goals of legal certainty and political stability, poses a potential threat to human rights. This study employs normative legal research techniques, library law research, and meticulous data collection to dissect the complexities surrounding the State Administrative Court's lawsuit filing deadline. The findings underscore the contentious nature of the 90-day limit, emphasizing its potential adverse effects on human rights and its perceived departure from its intended purposes. By elucidating these dimensions, the study aims to foster a deeper understanding of the controversy and its implications.